ab=-1.a+b=2,则 b/a+a/b=
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 21:20:09
ab=-1.a+b=2,则b/a+a/b=ab=-1.a+b=2,则b/a+a/b=ab=-1.a+b=2,则b/a+a/b=b/a+a/b=(b2+a2)/ab=[(a+b)2-2ab]/ab=(4
ab=-1.a+b=2,则 b/a+a/b=
ab=-1.a+b=2,则 b/a+a/b=
ab=-1.a+b=2,则 b/a+a/b=
b/a+a/b=(b2+a2)/ab=[(a+b)2-2ab]/ab=(4+2)/-1=-6
若a/b=2 则a*a-ab+b*b/a*a+b*b等于?
如果a/b=2则a*a-ab+b*b/a*a+b*b求值
a/b=2 ,(a*a-ab+b*b)/(a*a+b*b)=
ab=-1.a+b=2,则 b/a+a/b=
a×a+ab=18,ab+b×b=8,则a×a-b×b=
1/a+1/b=3则a-ab+b/a+2ab+b值是?
a^3-ab^2 =a (a^2 -b^2) =a(a+b)(a-b)
a(a-1)-(a×a-b)=-5,求(a×a+b×b)÷2-ab
(ab+b)(ab+b)-(a+b)(a+b)= (公式)
a(a+b)(a-b)-a(a+b)(a+b),其中(a+b)=1,ab=-1/2
1.已知1/a+1/b=4,则(a-3ab+b)/(2a+2b-7ab)=
若a/b=2,求分式a*a+ab-b*b/a*a-2ab+2b*b
已知a+2b=0,求a*a+2ab-b*b/2a*a+ab+b*b
ab/a+b=3 a-2ab+b/2a-3ab+2b?
a+b/ab= /a²b
已知a+b=10,ab=-2,则(3a+b)-(2a-ab)=?
已知a+b=10,ab=-2,则(3a+b)-(2a-ab)=?
(a+ab)-[(ab-2b)-a]-(-9ab),其中a+b=-7,ab=3.